If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -4.50x = 42.50 Solving 29 + -4.50x = 42.50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + -4.50x = 42.50 + -29 Combine like terms: 29 + -29 = 0 0 + -4.50x = 42.50 + -29 -4.50x = 42.50 + -29 Combine like terms: 42.50 + -29 = 13.5 -4.50x = 13.5 Divide each side by '-4.50'. x = -3 Simplifying x = -3
| 7x+5=5+2x+35 | | 5x^2+6x+3= | | 29-4.50x=52.5 | | A+8=2a-58 | | 6(g-2)+g=8g-20 | | 4x^2-17x+30=8x+5 | | 1.57=-logX | | 10d-80=20 | | 39x^2-474x-2460=0 | | x^16-y^6=0 | | (3w+4)+5(w-2)-3(6w-8)=10 | | 4x+224=136 | | 78x-474=0 | | 2a+3a+9= | | 8z^3-6z^2=72z-54 | | 4t+224=136 | | 3m^2+5m+7=0 | | 0.71=ln(y) | | 5(x+2)+5=15 | | 4.1a+9.98=-8.06 | | 2x+75=725 | | -(3w+4)+5(w+2)-3(6w-8)=10 | | 2x+69=819 | | 2(-5+2x)=x-1 | | (5y+8)(1+y)=0 | | b=y+ty | | -9=5+2y | | 3x^4-9x^3-1x^2=0 | | -335=-14x-125 | | (9-x)(9-x)=17 | | 166=2x-3(6x+18) | | 6x^2+14x-9x-21= |